Tiger grass (Thysanolaena maxima) cultivation in CALSANAG watershed in Romblon, Philippines: dilemmas and prospects for sustainable natural resources management (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Landicho LD, Ocampo MTNP, Cabahug RED, Baliton RS, Andalecio EV, Inocencio R, Servanez MV, Cosico RSA, Catillo AKA, Famisaran LDJ. 2020. Tiger grass (Thysanolaena maxima) cultivation in CALSANAG watershed in Romblon, Philippines: dilemmas and prospects for sustainable natural resources management. Biodiversitas 21: 2322-2330. Promoting sustainable natural resources management is a complex issue such that striking a balance between socioeconomic productivity and environmental integrity remains a challenge. This paper highlights the results of a study conducted from April to December 2019, which assessed the state of natural resources management in Barangay Mari-norte, San Andres, Romblon, which is part of the CALSANAG (Calatrava, San Andres, and San Agustin) Watershed. Biophysical characterization was done to determine land use and biodiversity, while farm household survey was administered to 133 farmers to characterize their socioeconomic conditions. Results showed that all of the farmer-respondents were engaged in the production of tiger grass (Thysanolaena maxima Roxb), where most of the farm households derived an estimated annual income of >Php50,000. Although their household income is higher as compared to other upland farming communities in the Philippines, most of them expressed that their income is insufficient since tiger grass is harvested only once a year, and the farmers have no alternative sources of income. On the other hand, biophysical characterization revealed the following: the farms are generally rainfed, have rolled to steep slopes, and have indications of low soil fertility, soil erosion incidence, and very low level of biodiversity (0.92). Most of the farmers practiced "slash-and-burn" to cultivate tiger grass as a single crop and hence, the forest cover has declined. A multi-agency collaboration jointly initiated agroforestry promotion in the upland farming communities through capability-building of upland farmers in agroforestry and establishment of tiger grass-based agroforestry model which showcases the economic and ecological viability of agroforestry systems in CALSANAG Watershed.
Keywords: Agroforestry model, biodiversity, upland farming communities, income, slash-and-burn